The Causal Effect of Air Pollution on International Tourist Arrivals - Rahman, Arief (Syntax Literate, 2020)
This paper adopts two approaches in examining the effects of air pollution on foreign tourist visits, namely instrumental variables and long-run growth, using dataset of 141 countries in period 2010-2017. The log of value added of industry per capita is used as an instrumental variable for the log of mean annual exposure of PM2.5 air pollution. Long-run growth of international tourist arrivals and mean annual exposure of PM2.5 air pollution are used in analyzing the long-run growth effect. The findings are that the level of air pollution has a negative influence on the number of foreign tourists visiting a country. Another finding is that the tourist arrival-air pollution elasticity has negative value and less than one. Keywords: Tourist, Air Pollution, IV, Long-Run Growth